Knowledge, Attitudes, and Practices Concerning COVID-19 in Bangladesh: A Qualitative Study of Patients With Chronic Illnesses - Razu, Shaharior Rahman; Nishu, Nishana Afrin; Rabbi, Md. Fajlay; Talukder, Ashis; Ward, Paul R. (Frontiers in Public Health, 2021)
The novel coronavirus disease (COVID-19) has posed a serious risk with pre-existing health conditions. This study was conducted to understand the knowledge, attitude, and practices concerning COVID-19 among patients with chronic illnesses in Bangladesh during the pandemic. The study was conducted in Khulna city of Bangladesh following a qualitative research design. We employed telephone interviews to collect data from 40 participants with four common pre-existing chronic illnesses (diabetes, hypertension, respiratory/asthma and heart disease). Findings show that majority of the participants had a moderate level of knowledge and an overall positive attitude regarding COVID-19 but appropriate safety practices were often ignored as the pandemic grows older. We also observed that the knowledge, attitude and practice regarding COVID-19 varied based on age, marital status, education, social class and rural/urban residence. We conclude that improving medical advice/support, promotion of awareness through mass media, strict monitoring of protective measures and subsidies from the government and self-consciousness could be effective strategies to mitigate the transmission of the disease and reduce risks for patients with chronic illness in Bangladesh during the COVID-19 pandemic.